E-tendering readiness in construction: an a priori model. (2018) - Al-Yahya, Moath; Skitmore, Martin; Bridge, Adrian; Nepal, Madhav P.; Cattell, David
To develop a conceptual model to assess the e-tendering readiness in any construction organisation prior to implementation. This involves a review of previous e-tendering models, the importance of e-tendering models for the construction industry and the requirements for developing e-TRMs. A model contains five themes: people, process, work environment, technology and service providers. The e-TRM themes consist of 13 constructs representing the basic items for e-tendering readiness. Ultimately, the e-TRM can be used worldwide; however, the model needs to be tested empirically for verification. To update previous IT/IS models by developing the themes that partially contribute to the research literature on traditional and electronic tendering and the body of knowledge in the construction industry. The service providers theme with its constructs (communication, market and technical) is proposed for the first time as a necessary support for successful e-tendering implementation.